Relationship of Academic Self-Efficacy With Anxiety in Completing Thesis in Final Year Students of Faculty of Education - Nasution, Rani Rahmita; Taufik, Taufik (Universitas Negeri Padang, 2024)
The thesis completion period for final year students is usually a stressor for students. This condition often causes anxiety and despair. Student anxiety in completing the thesis leads to disruption of psychological and behavioral response patterns. One way to utilize the potential that exists in students is self-confidence (self-efficacy), in order to reduce anxiety. This study aims to describe academic self-efficacy and student anxiety in completing the thesis and to test the relationship between the two. This study uses a quantitative method with a descriptive correlational approach. The sample consisted of 70 final year students selected using purposive sampling. The instrument used was a questionnaire with a Likert scale model. Hypothesis testing uses the product moment correlation formula. The research findings are: (1) The average anxiety score in completing a thesis is 119.8 or (64.77%) in the moderate category , (2) The average academic self-efficacy of students is 128.56 (64.28%) in the moderate category, (3) There is a very weak negative significant relationship between academic self-efficacy and anxiety in completing a thesis of -0.90 with a significance level of 0.457.